Transnational Displays of Parenting and Caring For Elderly Parents - Juozeliūnienė, Irena; Martinkėnė, Gintė; Budginaitė-Mačkinė, Irma (Vilnius University Open Series, 2020)
This chapter is set up to incorporate Finch’s idea of ‘display’ to examine how migrant parents, adult migrant children, and close significant persons perform a set of actions to convey to each other and the society at large that these are family-doing activities. The authors sought to demonstrate that the concept of ‘display’ could be applied to analyze transnational practices of parenting and caring for elderly parents in a quantitative way. The chapter draws on the data from a quotabased survey (N = 304) of three types of transnational families: mother-away and father-away with under-aged children living in Lithuania and adult child-away with elderly parents needing care living in Lithuania. The study was carried out in August 2018 as part of the research project ‘Global Migration and Lithuanian Family: Family Practices, Circulation of Care, and the Return Strategies’.